Ethical Problems of Digitalization and Artificial Intelligence in Education: a Global Perspective (Journal of Pharmaceutical Negative Results, 2023)
The purpose of the study is to analyze the ethical problems of the development of digital education in the context of the use of artificial intelligence systems as one of the leading trends in globalization. The research method is a theoretical analysis of the problems of the development of digital education and the use of artificial intelligence systems in the context of globalization problems. Globalization declares the importance of equal opportunities and similarity of processes and results of general and professional training of specialists from different countries. One of the technologies that ensure such equality or similarity is digital technologies that are being introduced into the process of general and vocational training and education. However, in addition to opportunities, the introduction of these technologies is accompanied by numerous ethical problems that call into question the economic feasibility of their widespread and uncontrolled creation and use.